PENGARUH VARIASI JENIS PENGOLAHAN TEH (Camellia sinensis L Kuntze) DAN KONSENTRASI GULA TERHADAP FERMENTASI KOMBUCHA SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOLOGI SMA - Imam Mahadi; Irda Sayuti; Irma Habibah (Program Studi Pendidikan Biologi, 2017)
ABSTRACT This study aims to determine the effect of variations in the type of processing of tea (Camellia sinensis L. Kuntze) and the concentration of sugar to ferment kombucha and draft Worksheet Students (LKPD) High School Biology.This study consisted of two phases. The first phase is making kombucha tea using the experimental method completely randomized design (CRD) consisting of 8 treatments and 3 replications. Parameters measured were reducing sugar, total acid concentration, pH and organoleptic levels. The results obtained were analyzed by ANOVA and a further test DMRT at 5% level. The second phase is the phase Design (draft) LKPD sourced from the research phase I. LKPD design consists of two stages, namely Analysis and Design LKPD. The results showed that variations in the type of processing tea and sugar concentration provides significant effect on reducing sugar, total acid concentration, pH and organoleptic levels. The greater the concentration of sugar, the greater the reduction sugar and total acid content of kombucha tea, and increasingly lace pH of the solution. As for organoleptic color, aroma, and taste the best there is on the treatment T1G3 (black tea, sugar 120 grams). The results of the study can be used as a draft Worksheet Students (LKPD) on the material of conventional biotechnology. Key words : Kombucha tea, Tea Processing Type Variation, Concentration Sugar, draft LKPD